Laparoscopic approach to early gastric cancer in a patient with a prior history of open right hepatectomy: a case report - Ko Ikegame; Makoto Hikage; Satoshi Kamiya; Yutaka Tanizawa; Etsuro Bando; Masanori Terashima (Surgical Case Reports)
Abstract Background Laparoscopic gastrectomy is regarded a standard treatment procedure for early gastric cancer and is widely used in clinical practice. However, the feasibility of laparoscopic gastrectomy for patients with a prior history of open surgery, especially in the case of a complicated operation, remains unclear. Here, we report a laparoscopic gastrectomy case with a prior history of right hepatectomy. Case presentation A 70-year-old man was diagnosed with early gastric cancers preceding a right hepatectomy for a solitary hepatocellular carcinoma at risk of rupture. An additional gastrectomy, after non-curative endoscopic submucosal dissection, was planned after the hepatectomy. Extensive adhesions were found around the liver. Rigid adherence of the duodenum to the adjacent hepatoduodenal ligament had formed. In addition, identification of the hepatic artery was difficult due to stiffening of the mesentery. Peeling off the adhesions from the ventral side of the duodenum revealed the supra-pyloric vessels and enabled us to transect the duodenum safely. Further, exposing the proper hepatic artery via the dorsal side of the mesentery and subsequent supra-pancreatic dissection on the outermost layer allowed effective identification of the right gastric artery. The postoperative course was uneventful. Conclusions We successfully performed total laparoscopic distal gastrectomy on a patient with a prior history of major hepatectomy.